Survei Kepuasan Masyarakat Terhadap Pelayanan Rumah Sakit Umum Daerah (RSUD) Gambiran Kota Kediri - Eko Wismanu, Rendra (Jurnal Ilmiah Administrasi Publik, 2018)
This research is a survey of public satisfaction on public service implementation at General Hospital (RSUD) Gambiran in Kediri City, which is specialized in Outpatient Installation (IRJ), Inpatient Installation (IRNA), and Support Services Unit. This survey was conducted as an evaluation material and to improve service at Gambiran Hospital in Kediri City. The method used in this research is quantitative descriptive, with data collection method of questionnaire and interview. The result of the satisfaction survey showed that from the service of Gambiran Hospital in Kediri City has good category, with the total index is 72,89. The detail of Outpatient Installation (IRJ) have index 71,13 with good category, Installation of Inpatient (IRNA) 74, 22 with good category, and Support Service Unit index of 73.32 with good category. Conclusion in this research is all service at Gambiran Hospital in Kediri City have good categories, but there are some element of service that need to be paid attention and repaired, such as service promise, infrastructure to support promise service, queue time and service delivery time, service officer attitude, and complaint and handling of complaint service.